@ -0,0 +1,105 @@ |
|||||
|
\documentclass{article} |
||||
|
\usepackage[utf8]{inputenc} |
||||
|
\usepackage{amsfonts} |
||||
|
\usepackage{amsthm} |
||||
|
\usepackage{amsmath} |
||||
|
\usepackage{enumerate} |
||||
|
\usepackage{hyperref} |
||||
|
\hypersetup{ |
||||
|
colorlinks, |
||||
|
citecolor=black, |
||||
|
filecolor=black, |
||||
|
linkcolor=black, |
||||
|
urlcolor=black |
||||
|
} |
||||
|
|
||||
|
% custom solution environment to set custom numbers |
||||
|
\theoremstyle{definition} |
||||
|
\newtheorem{innersolution}{Solution} |
||||
|
\newenvironment{solution}[1] |
||||
|
{\renewcommand\theinnersolution{#1}\innersolution} |
||||
|
{\endinnersolution} |
||||
|
|
||||
|
\title{Seminar exercises} |
||||
|
\author{ } |
||||
|
\date{February 2022} |
||||
|
|
||||
|
\begin{document} |
||||
|
\maketitle |
||||
|
|
||||
|
\begin{solution}{1.9}\ |
||||
|
\begin{enumerate}[1.] |
||||
|
\item Let $f(a) = u$, then $g(f(a)) = g(u)$, so $g \circ f$ is a function. |
||||
|
\item We can see that composition of functions is associative as follows:\\ |
||||
|
we know that $[ f \circ g](x) = f(g(x)), \forall x \in A$,\\ |
||||
|
so, |
||||
|
$$(h \circ [g \circ f])(x) = h([g \circ f](x)) = h(g(f(x)))$$ |
||||
|
\\ |
||||
|
and |
||||
|
$$([h \circ g] \circ f)(x) = [h \circ g](f(x)) = h(g(f(x)))$$ |
||||
|
Then, we can see that $$h \circ (g \circ f) = h(g(f(x))) = (h \circ g) \circ f$$ |
||||
|
\end{enumerate} |
||||
|
\end{solution} |
||||
|
|
||||
|
\begin{solution}{1.28}\ |
||||
|
|
||||
|
The quotient set of the equivalence relation in Example 1.27 is |
||||
|
$$ |
||||
|
X / \sim = \{[(x_0,y_0)], [(x_1, y_1)], \ldots, [(x_n, y_n)]\} |
||||
|
$$ |
||||
|
Yes, it is isomorphic to the cosets of the \emph{nth} roots of unity, which are $\mathbb{G}_n = \{w_k\}^{n-1}_{k=0}$, where $w_k=e^{\frac{2 \pi i}{n}}$. |
||||
|
\end{solution} |
||||
|
|
||||
|
\begin{solution}{2.2}\ |
||||
|
|
||||
|
To prove that the inverse $x^{-1}$ is unique, assume $x^{-1}$ and $\tilde{x}^{-1}$ are two inverses of $x$.\\ |
||||
|
By the definition of the inverse, we know that $x \cdot x^{-1} = e$. And by the definition of the unit element, we know that $x \cdot e = x$.\\ |
||||
|
Then, $$x^{-1} \cdot (x \cdot \tilde{x}^{-1}) = x^{-1} \cdot e = x^{-1}$$ |
||||
|
and $$(x^{-1} \cdot x) \cdot \tilde{x}^{-1} = e \cdot \tilde{x}^{-1} = \tilde{x}^{-1}$$ |
||||
|
By associativity property of groups, we know that |
||||
|
$$x^{-1} \cdot (x \cdot \tilde{x}^{-1}) = (x^{-1} \cdot x) \cdot \tilde{x}^{-1}$$ |
||||
|
so, $$x^{-1} \cdot e = e \cdot \tilde{x}^{-1}$$ |
||||
|
which is $$x^{-1} = \tilde{x}^{-1}$$ |
||||
|
So, for any $x \in G$, the inverse $x^{-1}$ is unique. |
||||
|
\end{solution} |
||||
|
|
||||
|
\begin{solution}{2.5}\ |
||||
|
|
||||
|
Let $\alpha = (\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix})$, $\beta = (\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix})$, then, |
||||
|
$$ |
||||
|
\alpha \cdot \beta = |
||||
|
(\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix}) |
||||
|
\cdot (\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix}) |
||||
|
= (\begin{smallmatrix}1 & 2 & 3\\ 3 & 2 & 1\end{smallmatrix}) |
||||
|
$$ |
||||
|
|
||||
|
and |
||||
|
$$ |
||||
|
\beta \cdot \alpha = |
||||
|
(\begin{smallmatrix}1 & 2 & 3\\ 3 & 1 & 2\end{smallmatrix}) \cdot |
||||
|
(\begin{smallmatrix}1 & 2 & 3\\ 1 & 3 & 2\end{smallmatrix}) |
||||
|
= (\begin{smallmatrix}1 & 2 & 3\\ 2 & 1 & 3\end{smallmatrix}) |
||||
|
$$ |
||||
|
|
||||
|
So, we can see that |
||||
|
$$ |
||||
|
(\begin{smallmatrix}1 & 2 & 3\\ 3 & 2 & 1\end{smallmatrix}) |
||||
|
\neq |
||||
|
(\begin{smallmatrix}1 & 2 & 3\\ 2 & 1 & 3\end{smallmatrix}) |
||||
|
$$ |
||||
|
|
||||
|
so, $\alpha \cdot \beta \neq \beta \cdot \alpha$. |
||||
|
\end{solution} |
||||
|
|
||||
|
\begin{solution}{2.26}\ |
||||
|
|
||||
|
We want to prove that $f: G \rightarrow H$ is a \emph{monomorphism} iff $\ker f=\{e\}$.\\ |
||||
|
We know that $f$ is a \emph{monomorphism} (\emph{injective}) iff $\forall a, b \in G$, $f(a) = f(b) \Rightarrow a = b$.\\ |
||||
|
Let $a, b \in G$ such that $f(a)=f(b)$. Then |
||||
|
$$f(a) f(b)^{-1} = f(b) (f(b))^{-1} = e$$ |
||||
|
$$f(a) f(b^{-1}) = e$$ |
||||
|
$$f(ab^{-1}) = e$$ |
||||
|
as $\ker f = \{e\}$, then we see that $ab^{-1}=e$, so $a=b$. Thus $f$ is a \emph{monomorphism}. |
||||
|
\end{solution} |
||||
|
|
||||
|
\end{document} |